Phytotoxicity of Cedrus and Pelargonium essential oils on selected weeds (Annals of the Institute of Biology, 2022)
The inhibitory effects of Cedrus atlantica and Pelargonium graveolens essential oils on seed germination and seedling growth of three weed species were investigated. The oils were applied in three different concentrations (10, 20 and 30 µg/mL) in laboratory conditions, with four replications. Applied oils demonstrate a strong inhibitory effect on Taraxacum officinale in the tested concentrations with a germination inhibition percentage ranging from 50-100%. The tested oils were considerably less effective on Chenopodium album and Daucus carota seeds, suggesting their usage as natural herbicidal products for some weed species.